Digital Transformation in Islamic Banking Services as a Support for Green Banking Practices - Miftahur Rahman; Ririn Makrifah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Digital transformation has become a key factor in improving the efficiency and quality of Islamic banking services, while supporting green banking practices that are oriented towards environmental sustainability. This research aims to analyze the role of digitalization in Islamic banking services in supporting the implementation of green banking. The method used in this study is a qualitative approach with literature study and secondary data analysis from various reliable sources. The results of the study show that digitalization in Islamic banking, such as the use of mobile banking, paperless transactions, and the implementation of artificial intelligence in risk analysis, contributes significantly to reducing natural resource consumption and increasing operational efficiency. In addition, sharia-based financial technology innovations also encourage transparency and public trust in environmentally friendly banking products. The study concludes that digital transformation not only increases the competitiveness of Islamic banking in the industrial era 4.0, but also strengthens the commitment to the principles of sustainability and Islamic business ethics.